2021
DOI: 10.3389/fpsyt.2021.664204
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Psychiatric Emergency Visits, but Stable Addiction Emergency Visits, During COVID-19—A Time Series Analysis 10 Months Into the Pandemic

Abstract: Background: The COVID-19 pandemic has been suspected to increase mental health problems, but also to possibly lead to a decreased treatment seeking, for example due to fear of attending hospital. Early findings demonstrate decreased treatment seeking for mental health, which may differ across diagnostic groups. This study aimed to examine treatment uptake at a general psychiatry emergency unit and at an addiction psychiatry emergency unit in Malmö, Sweden, separately. In addition, the study aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
(26 reference statements)
6
17
1
Order By: Relevance
“…The largest absolute reduction among the different psychiatric diagnoses was seen among patients with substance abuse disorders and those with neurotic, stress-related, and somatoform disorders. A recent study at another large Swedish hospital reported similar results in patients with unipolar and anxiety-related disorders but, contrary to our results, the number of contacts related to substance use disorders remained unaltered ( 15 ). The mean weekly PEVs for patients with no diagnosis were numerically small during all time periods.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The largest absolute reduction among the different psychiatric diagnoses was seen among patients with substance abuse disorders and those with neurotic, stress-related, and somatoform disorders. A recent study at another large Swedish hospital reported similar results in patients with unipolar and anxiety-related disorders but, contrary to our results, the number of contacts related to substance use disorders remained unaltered ( 15 ). The mean weekly PEVs for patients with no diagnosis were numerically small during all time periods.…”
Section: Discussioncontrasting
confidence: 99%
“…The unaltered number of PEVs among patients with schizophrenia and other related psychotic disorders stands in contrast to a report by the National Board of Health and Welfare in Sweden where other Swedish regions showed an increased rate of visits among patients with this psychiatric diagnosis ( 12 ). On the other hand, there are studies that show similar results to ours with either no significant reduction in this patient group ( 15 , 24 ) or a smaller absolute reduction compared to other diagnoses ( 11 ). The largest absolute reduction among the different psychiatric diagnoses was seen among patients with substance abuse disorders and those with neurotic, stress-related, and somatoform disorders.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall treatment-seeking within the mental health care system was unaffected and constant in numbers over the last years, while the number of new psychiatric patients decreased after the COVID-19 outbreak. In line with these findings, another study observed decreased contact to the health care system regarding acute cases of depression and anxiety (19).…”
Section: Introductionsupporting
confidence: 57%
“…On the other hand, a negatively affected public mental health state and impaired possibilities to seek help could potentially compensate each other in the recorded dispensed amounts of psychotropic medication and hence become undetectable by this study design. As mentioned in the introduction, several studies in Sweden suggest a deterioration in mental health and a compromised access to mental health care (16)(17)(18)(19). Especially new and acute patients seem to be affected, perhaps struggling the most with searching help while avoiding physical contact during the pandemic.…”
Section: Discussionmentioning
confidence: 99%